2017
DOI: 10.14426/ahmr.v3i2.831
|View full text |Cite
|
Sign up to set email alerts
|

The Owners of Xenophobia: Zimbabwean Informal Enterprise and Xenophobic Violence in South Africa

Abstract: This paper is a contribution to our understanding of the intertwined economic and political crises in Zimbabwe and the crisis of xenophobia in South Africa. There have been few studies to date specifically examining the impact of xenophobic violence on Zimbabweans trying to make a living in the South African informal economy. The paper first provides a picture of Zimbabwean migrant entrepreneurship using survey data from a 2015 study of migrants in the informal economy. All of the Zimbabwean entrepreneurs inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…South Africa has high levels of gender-based violence and, increasingly, xenophobia, and migrant women are also victims of such violence (Lefko-Everett, 2011, p. 277; Sigsworth, 2010, p. 2). There are common misconceptions that African migrants import diseases and crime, steal jobs and opportunities, and drain the health care system and other state resources (Crush et al, 2017, p. 21; Dodson, 2010, p. 5). Institutional xenophobia has also been widely reported in literature, implicating institutions such as the police department for frequently intimidating and arresting migrants through targeted operations (Opfermann, 2019, p. 7).…”
Section: Background Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…South Africa has high levels of gender-based violence and, increasingly, xenophobia, and migrant women are also victims of such violence (Lefko-Everett, 2011, p. 277; Sigsworth, 2010, p. 2). There are common misconceptions that African migrants import diseases and crime, steal jobs and opportunities, and drain the health care system and other state resources (Crush et al, 2017, p. 21; Dodson, 2010, p. 5). Institutional xenophobia has also been widely reported in literature, implicating institutions such as the police department for frequently intimidating and arresting migrants through targeted operations (Opfermann, 2019, p. 7).…”
Section: Background Contextmentioning
confidence: 99%
“…Previous studies that show the migration pattern from Zimbabwe to South Africa suggest that one of the drivers of migration over the past two decades has been the country’s political instability and ailing economy (Bloch, 2010; Crush et al, 2017; McDuff, 2015). The data is similar to a study that examined the reasons that influenced Zimbabwean women to leave and concurs that economic difficulties in the form of poverty and unemployment are the key migration “push factors” for female Zimbabwean migrants (Lefko-Everett, 2010, p. 269).…”
Section: Forms Of Vulnerabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…While South Africa may be one of the most advanced economies within the emerging African economies, it is also saddled with serious socio-economic challenges such as high unemployment rate and high poverty levels and has the world’s highest level of socio-economic inequality as measured by a Gini co-efficient (World Bank, 2018). Naturally, these challenges have created an environment where anti-immigration sentiments have mutated into xenophobia against African migrants (Crush et al , 2017; Gordon, 2020). Considering this adverse context, the findings of this study may potentially help South African policy makers better understand and apply measures to advance immigrant entrepreneurship.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, a study conducted by Cinini 8 has demonstrated that having the appropriate legal status is not a guarantee to secure a job in Durban and that foreign nationals who have legal documentation still face discrimination in governmental and private institutions, not only for jobs but for other services earmarked for them as migrants. For instance, Crush and Tawodzera 9 report that migrants and refugees face severe obstacles in accessing loans from formal sources in South Africa as they require collateral. To that end, Moagi et al 10 confirm that, in South Africa, xenophobia has damaged the informal employment sector, resulting in higher unemployment rates due to the displacement and burning of immigrant shops that employed South Africans.…”
Section: Introductionmentioning
confidence: 99%